Pemodelan dan Simulasi Perbaikan Harmonisa Menggunakan Double Tuned Filter di Laboratorium Teknik Elektro Universitas Negeri Medan - M. Zaky Noufal; Azmi Rizki Lubis; Marwan Affandi (E-JOINT (Electronica and Electrical Journal Of Innovation Technology), 2025)
The Basic Electrical Engineering Laboratory of Medan State University uses many nonlinear loads such as computers, laptops, printers, scanners, projectors, inverters, converters and others that can cause harmonics. The method used to overcome harmonics is by using a double tuned passive filter, the use of a double tuned filter has an effect on reducing current harmonics and overcoming the increase in cos phi values ​​in the electrical system. A double tuned filter can be a broader strategy in managing power factors by reducing certain harmonic orders, but it cannot directly improve the overall power factor without carefully considering the system conditions and existing problems. By inputting the filter requirement values ​​F,,, , Ω the simulation results obtained are a decrease in harmonic levels, where the third order harmonic which was originally 28.3% fell to 19.77% and the fifth order harmonic which was originally 13.27% fell to 9.27%. The reliability of using a double tuned filter to increase the desired power factor of 0.95 by compensating for the known reactive power of Qc = 794.206846 Var. The use of passive filters is very feasible to be used in reducing harmonic disturbances that occur in the electric power system.